Belajar Bahasa Jepang Melalui Manga: Fokus pada Pemerolehan Onomatope - Idrus, Idrus (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2024)
Mastering vocabulary is crucial to learning foreign languages, which is also true for Japanese. One of the many ways to acquire Japanese vocabulary is through various media, such as manga. Manga is rich in onomatopoeias, a valuable tool for enhancing one's grasp of Japanese vocabulary. Onomatopoeias are imitations of sounds that help convey a particular state or condition, allowing the reader or listener to imagine and even